Occurrence and antimicrobial susceptibility of enteric rods and pseudomonads isolated from the dental prostheses biofilm - Sanrrangers Sales Silva; Maximilo de Oliveira Ribeiro; Francisco Isaac Fernandes Gomes; Hellíada Vasconcelos Chaves; Antonio Alfredo Rodrigues e Silva; Iriana Carla Junqueira Zanin; Francisco Cesar Barroso Barbosa (Journal of Applied Oral Science)
ABSTRACT Aspiration of oral bacteria leads to cardiac and respiratory infectious diseases and dentures can act as a reservoir for pathogenic microorganisms. Objective: To determine the occurrence and the in vitro antimicrobial susceptibility of enteric rods and pseudomonads from the denture biofilm of 52 subjects at the Center for Dental Specialties of Sobral/ Ceara, Brazil. Material and Methods: Denture biofilm was collected and samples plated on MacConkey agar. The isolated bacterial colonies were identified using the BBL Crystal enteric/non-fermenter system. Antibiotic bacterial susceptibility was assessed by the disc diffusion method of amoxicillin, amoxicillin/clavulanic acid, doxycycline, tetracycline, tobramycin, imipenem, cefotaxime, and ciprofloxacin. The Minimum Inhibitory Concentration (MIC) of cefotaxime, tobramycin, doxycycline, imipenem, and ciprofloxacin was determined for 40 species by E-test. Results: 34 subjects (65.4%) harbored enteric rods in their prostheses. Klebsiella pneumoniae (26.5%), Escherichia coli (23.5%), and Enterobacter aerogenes (23.5%) were the most prevalent species. All organisms were susceptible to ciprofloxacin and most species were resistant to amoxicillin or amoxicillin/clavulanic acid, demonstrating variable sensitivity patterns to other antimicrobials. However, the MIC showed the emergence of strains with reduced sensitivity to ciprofloxacin (MIC90≥3 μg/ mL) and cefotaxime (MIC90≥2 μg/mL). Conclusion: The findings show high prevalence of nosocomial diseases-related bacterial species and low susceptibility to antimicrobial drugs. Therefore, these results imply caution against the indiscriminate use of broad spectrum antibiotics in dental practice.